Musculoskeletal disorders among secondary school teachers in Douala, Cameroon: The effect of the practice of physical activities - Mekoulou Ndongo, Jerson; Bika Lele, Elysée Claude; Guessogo, Wiliam Richard; Meche, Laurence Patricia; Ayina Ayina, Clarisse Noel; Guyot, Jessica; Zengue, Babette; Lobe Tanga, Marie Yvonne; Owana Manga, Léon Jules; Temfemo, Abdou; Barth, Nathalie; Bongue, Bienvenu; et al. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Musculoskeletal disorders (MSDs) constitute an important public health in both developed and developing countries and are present in many work sectors, even education. The regular practice of physical activity (PA) is known to exert preventive effects on the occurrence of MSDs. Objective: The aim of this study is to determine the prevalence of MSDs and the preventive impact of PA on their occurrence among secondary school teachers. Participants and Methods: A cross-sectional study was conducted among 179 teachers in five government secondary schools in Douala, Cameroon. The Nordic and the Ricci-Gagnon questionnaires were used to determine MSDs and to assess the level of PA. Results: The 12-month and 7-day prevalence of MSD (PMSD-12m and PMSD-7d) were 84.3 % and 69.3 % respectively. The body regions more affected by MSDs were neck (PMSD-12m =54.2%, PMSD-7d=33.5%), lower back (PMSD-12m =43%, PMSD-7d=33%) and shoulders (PMSD-12m =35%, PMSD-7d =22.9%). Male were protected against MSDs (OR = 0.37; 95% CI 0.16 – 0.93; p = 0.04) during the last 12 months. The risk of MSDs during the last seven days was higher in teachers aged 30-40 years (OR = 2.86; 95% CI 1.14 – 7.14; p = 0.02) and 40-50 years (OR = 4.28; 95% CI 1.49 – 16.29; p = 0.008). This risk was tripled (OR = 3.07; 95% CI 1.40 – 6.78; p = 0.005) in inactive teachers compared to active. Conclusion: MSDs are a reality among teachers in secondary schools with high prevalence and were associated to age, gender, and PA.